Climatic changes during the Plio-Pleistocene transition as recorded by the isotopic composition of pedogenic carbonates - Beilinson, Elisa (2019)
Plio-Pleistocene continental deposits in south-eastern Buenos Aires province (Argentina), correspond to fluvioalluvial deposits interbedded with palaeosols. The Pliocene units show little participation of carbonatic features in their palaeosols, which are classified as Argillisols. The late Pliocene-Pleistocene palaeosols show a much higher participation of pedogenic carbonates and are classified as Calcisols. Could this change from Argillisols to Calcisols be related to the global-scale climatic change during the Plio-Pleistocene boundary?